Whole arm deletions of 18p: Medical and developmental effects. (14th January 2015) - Sebold, Courtney; Soileau, Bridgette; Heard, Patricia; Carter, Erika; O'Donnell, Louise; Hale, Daniel E.; Cody, Jannine D.
<x xml:space="preserve">Abstract</x> Deletions of the short arm of chromosome 18 have been well‐described in case reports. However, the utility of these descriptions in clinical practice is limited by varied and imprecise breakpoints. As we work to establish genotype–phenotype correlations for 18p‐, it is critical to have accurate and complete clinical descriptions of individuals with differing breakpoints. In addition, the developmental profile of 18p‐ has not been well‐delineated. We undertook a thorough review of the medical histories of 31 individuals with 18p‐ and a breakpoint in the centromeric region. We collected developmental data using mailed surveys and questionnaires. The most common findings included neonatal complications; cardiac anomalies; hypotonia; MRI abnormalities; endocrine dysfunction; strabismus; ptosis; and refractive errors. Less common features included holoprosencephaly and its microforms; hearing loss; and orthopedic anomalies. The developmental effects of the deletion appear to be less severe than reported in the literature, as average IQ scores were in the range of borderline intellectual functioning. Based on responses to standardized questionnaires, it appears this population has marked difficulty with activities of daily living, though several young adults were able to live independent of their parents. This manuscript represents the most comprehensive description of a cohort of 18p‐ individuals with identical breakpoints. Despite identical breakpoints, a great deal of phenotype variability remained among this population, suggesting that many of the genes on 18p‐ cause low‐penetrance phenotypes when present in a hemizygous state. Future efforts will focus on the clinical description of individuals with more distal breakpoints and the identification of critical regions and candidate genes. © 2015 Wiley Periodicals, Inc.